(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
Under the heading "Reviews and reports" can be found reviews of recently published volumes or essays, which are part of the issues and reflections of ecdotic practices. In addition, individual publications or indexes of entire magazine numbers will be presented if, for their arguments, are in dialogue, however in a dialogue at a distance, with the "pages" of PEML and their readers. Readers are invited to send specific reports to the editors, which will be evaluated and published. Finally, in this section we will present the syntheses, given as "reports", of lectures and seminars, whose contents come into direct comparison with the issues at the center of the magazine’s reflections.